Homemade hydroponic gardens, an environmental undertaking in the municipality of Pasto (Business Vision, 2020)
Hydroponics is a revolutionary cultivation technique due to its minimal or null use of resources, revealing itself as a solution of sustainability without possible comparison with traditional agriculture. It can be a safe and efficient alternative for growing different foods in large quantities. It is said that hydroponics is consolidated as a type of agriculture with great future prospects, for new crops in reduced spaces; therefore the present project aims to identify the feasibility of introducing hydroponic crops in the urban area of the city of San Juan de Pasto; This project is complemented with additional studies, such as the market study that helped identify potential customers for the company, the technical study that identified the installed capacity of the company and the potential demand, the administrative study helped to determine the type     of organization, gerearchies policies and standards on which the company is based and the socio-environmental study helped to identify the social responsibility of the company with the environment and the impact that will have the products and services offered by the company in the environment and the financial study that is underway will help the return on investment in the project which will determine the feasibility of the project. The present research is a quantitative paradigm, descriptive type, analytical empirical approach and deductive method.
Keywords: cultivation; water; plants; hyphroponics; sustainability